UNNOTICED ETIOLOGY IN ORTHOPEDIC COMPLAINTS: CHRONIC MOUNTAIN SICKNESS - Kayahan Karaytuğ; Mehmet Ekinci; Altuğ Yücekul (İstanbul Tıp Fakültesi Dergisi)
Objective: Chronic mountain sickness (CMS) is a clinical syndrome with symptoms of polycythemia that may interfere with other nonspecific diseases. The current study aimed to investigate the symptoms of patients living at high altitudes, who initially presented complaints that seemed to be common orthopedic problems, and to examine their relationship with chronic mountain sickness. Material and Methods: The prospectively collected data of 104 patients were retrospectively evaluated for serum hemoglobin (Hb) and hematocrit (Hct) levels, oxygen saturation (sO2), Qinghai CMS questionnaire score, alcohol and tobacco use, “any history of acute mountain sickness, body mass index (BMI), blood pressure, heart rate, and duration of high-altitude living. Patients grouped according to the Qinghai score as healthy, mild, moderate or severe CMS. The groups were investigated in terms of parameters and demographic characteristics. Results: Of the 104 patients, 33 (31.7%) had a mild CMS score ≥6 (28 patients, 6–10, 5 patients, 11–14 points); remaining patients had no CMS. The frequency of excessive erythrocytosis was 4.5% in men and 3.3% in women. There was a significant difference in Hb, Hct and sO2 levels between the healthy and mild CMS groups (p<0.001). CMS score had a positive correlation with Hct (rho 0,381 p<0.001) and negative correlation between sO2 levels (rho -0.432 p<0.001). Conclusions: CMS can be observed at lower altitudes than described in literature. In individuals living in high altitudes, some of the CMS symptoms may be confused with real orthopedic symptoms and orthopedists working in these areas should increase their awareness on this issue. In order to make an appropriate approach, other symptoms related to CMS should be questioned in patients living at high altitudes.